REVIEW OF THE SECURITY AND CONFIDENTIALITY OF ELECTRONIC MEDICAL RECORDS AT UPTD PUSKESMAS KEDAWUNG IN 2025 - Finliana, Shelomita Cahya; Subianto, Totok; Elfi; Karmanto, Bambang (JURNAL KESEHATAN, SAINS, DAN TEKNOLOGI (JAKASAKTI), 2025)
Medical records are confidential documents that need to be preserved because they contain a complete record of the patient's treatment and care process from beginning to end. To ensure the information it is necessary to support the security and confidentiality system in electronic medical records.  This study aims to determine the security and confidentiality of electronic medical records with aspects of confidentiality, integrity, and availability at UPTD Puskesmas Kedawung. This type of research uses a type of qualitative method. The method used to collect data is by using in-depth interviews and observation. The subjects of this study consisted of 3 people, namely the head of the Kedawung Puskesmas, the medical records coordinator, and the medical records officer. The results showed that there is no specific SOP that regulates the security and confidentiality of the RME. In addition, access rights are given to all officers so that they can access other sections as well.